2014
DOI: 10.1002/crat.201400200
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effect of solvent polarity on the habit modification of monoclinic paracetamol in terms of molecular recognition at the solvent crystal/interface

Abstract: The habit change of monoclinic paracetamol crystallized from solutions with different solvents such as water, ethanol, methanol, acetone, isopropyl alcohol, tetrahydrofuran, cyclohexanone, acetonitrile and 1, 4 ‐ dioxane was investigated. Change in solubility, pH and nucleation time of paracetamol in these solvents at ambient condition was studied. The polymorphic form of the nucleated paracetamol was observed under in‐situ optical microscopy. Solutions with different solvents having different chemical nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…More detailed studies ( 99 ) were performed on the crystal habit of acetaminophen for solvents with different polarities. For polar protic solvents, it was found that their affinity towards facets favouring hydrogen bonding slowed the growth rate of those facets, since the sites were less prone to interact with solute molecules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More detailed studies ( 99 ) were performed on the crystal habit of acetaminophen for solvents with different polarities. For polar protic solvents, it was found that their affinity towards facets favouring hydrogen bonding slowed the growth rate of those facets, since the sites were less prone to interact with solute molecules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 28,31 ] Creation of supersaturation within the solution mainly depends on the rate of solvent evaporation at constant temperature and is inevitable in solvent evaporation solution growth technique. [ 17,19,32 ] When solvent molecules evaporate from the solution that attains supersaturation and is trying to reach the thermodynamic equilibrium or stability, henceforth, growth occurs followed by the formation of structured critical nuclei. Growth and perfection of the end crystal not only depend on the supersaturation, but also on the anisotropic growth behavior of the crystal which is very much influenced by the solvent molecules through the formation of solid‐liquid interface (solute‐solvent) potential barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Its solubility increases with an increase in EtOH concentration up to a maximum of 80% v/v EtOH/H2O before the solubility of PAR decreases (Jiménez and Martínez, 2006). The morphology of PAR is greatly influenced by the method of crystallisation, solvent used, temperature, pressure and supersaturation rate (Sudha and Srinivasan, 2014). We have recently demonstrated that the size and morphology of spray dried paracetamol can be controlled through the selection of spray dryer inlet temperature, solvent composition and corresponding atomised droplet characteristics (McDonagh and Tajber, 2019).…”
Section: Introductionmentioning
confidence: 99%